(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the role of word acquisition in enriching the language lexicon. Opinions are expressed about the transfer of the borrowings from Arabic, Persian-Tajik, Russian and other languages, and through what factors they entered. Opinions of famous scientists about word acquisition are expressed. The relationship between the word acquisition process and language styles is analyzed. Through the properties of native words, it is shown that the cooperation of our people with the peoples of other languages is deep. It was mentioned that words from the Persian-Tajik language, Arabic, Russian, Mongolian and Chinese were also included in the Uzbek language dictionary. Also, in what period and through what factors the word was acquired, it is covered in detail. It is noted through examples that words in each language have their own signs.